CLINICAL PROFILE, RISK FACTORS, AND PULMONARY FUNCTION TESTS IN PATIENTS OF OBSTRUCTIVE SLEEP APNEA - GUGULOTH MANOSRI SOWMYA; A MOUNIKA; B BHANU REKHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of this study was to analyze clinical profile, risk factors, and pulmonary function test (PFT) in patients with obstructive sleep apnea (OSA). Methods: This was a prospective study undertaken in the department of pulmonary medicine of a tertiary care medical institute in which adult patients OSA were included on the basis of a predefined inclusion and exclusion criteria. Demographic details of patients were noted. Gender distribution, age distribution, clinical profile, and risk factors were studied. Severity of OSA was assessed by apnea hypopnea index (AHI). PFTs were done in all the cases. Results: Out of 60 studied cases, there were 39 (65.00%) males and 21 (35.00%) females with a M: F ratio of 1: 0.53. The mean age of the studied cases was 51.58±11.14 years. The most common risk factor present in studied cases was increased neck circumference. Severity of OSA, as determined by AHI, was found to be mild, moderate, and severe in 34 (56.67%), 20 (33.33%), and 6 (10.00%) patients, respectively. Snoring that was bothersome to others was the most common presenting complaints in studied cases and was found in 52 (86.67%) cases. PFT was normal in 23 (38.33%) patients whereas obstructive as well as restrictive features were seen in 16 (26.67%) and 14 (23.33%) patients, respectively. Conclusion: PFTs should be included during workup of patients with OSA and obstructive lung disease may coexist and cause an increase in mortality.